PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DANAMAS MANDIRI INVESTA (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of work environment and work discipline on employee performance at PT. Danamas Mandiri Investa. This type of research is quantitative. The population of this study were employees of PT. Danamas Mandiri Investa. The analysis used is a quantitative technique using a saturated sampling technique with a total population of 30 respondents. The instrument of this research is a questionnaire. The results of the research instrument test using multiple regression analysis test, t test, and f test. The results of the analysis show that the work environment and work discipline have a significant effect on employee performance with the results of multiple regression analysis of Y = 6.427 + 0.509 X1 + 0.331 X2. The results of the t-test of the work environment obtained the results of t-count 4.315 > t-table 2.051, meaning that Ho1 was rejected, and Ha1 was accepted, the t-test of work discipline obtained the results of t-count 2.286 > t-table 2.051, meaning Ho2 was rejected and Ha2 was accepted, and the results of the F-test were 12.859 > F Table 3.34 means that Ho3 is rejected and Ha3 is accepted. Based on the results of these data, it can be concluded that the work environment and work discipline affect the performance of employees at PT. Danamas Mandiri Investa.